SHANK3 in vagal sensory neurons regulates body temperature, systemic inflammation, and sepsis - Zhang, Linlin; Bang, Sangsu; He, Qianru; Matsuda, Megumi; Luo, Xin; Jiang, Yong-Hui; Ji, Ru-Rong (Frontiers in Immunology, 2023)
Excessive inflammation has been implicated in autism spectrum disorder (ASD), but the underlying mechanisms have not been fully studied. SHANK3 is a synaptic scaffolding protein and mutations of SHANK3 are involved in ASD. Shank3 expression in dorsal root ganglion sensory neurons also regulates heat pain and touch. However, the role of Shank3 in the vagus system remains unknown. We induced systemic inflammation by lipopolysaccharide (LPS) and measured body temperature and serum IL-6 levels in mice. We found that homozygous and heterozygous Shank3 deficiency, but not Shank2 and Trpv1 deficiency, aggravates hypothermia, systemic inflammation (serum IL-6 levels), and sepsis mortality in mice, induced by lipopolysaccharide (LPS). Furthermore, these deficits can be recapitulated by specific deletion of Shank3 in Nav1.8-expressing sensory neurons in conditional knockout (CKO) mice or by selective knockdown of Shank3 or Trpm2 in vagal sensory neurons in nodose ganglion (NG). Mice with Shank3 deficiency have normal basal core temperature but fail to adjust body temperature after perturbations with lower or higher body temperatures or auricular vagus nerve stimulation. In situ hybridization with RNAscope revealed that Shank3 is broadly expressed by vagal sensory neurons and this expression was largely lost in Shank3 cKO mice. Mechanistically, Shank3 regulates the expression of Trpm2 in NG, as Trpm2 but not Trpv1 mRNA levels in NG were significantly reduced in Shank3 KO mice. Our findings demonstrated a novel molecular mechanism by which Shank3 in vagal sensory neurons regulate body temperature, inflammation, and sepsis. We also provided new insights into inflammation dysregulation in ASD.